Titan Unveiled : Saturn's Mysterious Moon Explored - Lorenz, Ralph, 1969- (Book collections on Project MUSE., 2010)
Provides an insider's account of the scientific community's first close encounter with an alien landscape. The authors describe Titan as a world strikingly like Earth, and tell how Titan may hold clues to the origins of life on our own planet and the possibility of its presence on other worlds.